Transformation of physical, physicochemical and chemical properties of raised bed soil profiles under different elapsed time in a lowland ecosystem - PATRA, S. K.; PRAMANIK, SANJIT; RAY, R. (Journal of Soil and Water Conservation, 2021)
Representative soil profiles, one from prevailing lowland and three from different aged raised bed land were collected from the Dankuni basin of West Bengal with a view to assess the variations in physical, physicochemical and chemical properties of raised bed soils with respect to time as compared with the that of lowland soils. The results showed that in spite of severe disturbances while raised bed-pond structure construction, there was consistent improvement in the physical, physicochemical and chemical environment of raised bed soils with passage of time and the effect was more pronounced with advanced stages than the recent development in the existing lowland. The technology of raised bed-pond configuration, besides ensuring drainage in monsoon and providing assured irrigation in post monsoon, would likely to recover the soil health for stainable crop production.